RELATIONSHIP BETWEEN PaCO2 LEVELS AND CLINICAL OUTCOMES OF ACUTE ISCHEMIC STROKE PATIENTS WITH DECREASED OF CONSCIOUSNESS - Andre Lona, Aldy Saffrudin Rambe & Cut Aria Arina (International Journal of Research Science and Management, 2019)
Background: Stroke is a leading cause of mortality and disability worldwide. Changes in Partial Pressure of Carbon Dioxide (PaCO2) in patients with acute ischemic stroke can worsen the ischemic condition in cerebral and clinical outcomes. Objective: To determine the relationship between PaCO2 levels and clinical outcomes of acute ischemic stroke patients with decreased awareness. Research Methods: This study uses a cross-sectional design. Sampling was conducted at H. Adam Malik General Hospital Medan. Samples were taken as many as 46 subjects consecutively. The independent variable of the study is the level of PaCO2 and the dependent variable is the clinical outcome. Data analysis using the Spearman correlation test. Results: The characteristics of the study subjects consisted of men (43.5%) and women (56.5%) with an age range of 51-60 years, Batak ethnicity, high school education level, and decreased levels of PaCO2. The level of PaCO2 of research subjects had a mean of 37.39 mmHg ± 8.04. The median value of mRS in 7 treatment days was 4 (2-6). The most out of the disability mRS category was moderate disability of 28.3%. There is a significant relationship between PaCO2 with an increase in the value of mRS within 7 days of treatment and the strength of the correlation is relatively moderate. (p = 0.001; r 0.499). Conclusion: there is a significant relationship between PaCO2 with an increase in the value of mRS within 7 days of treatment